Safety and efficacy of health supplement for weight loss - Saliza Ibrahim; June Choon Wai Yee; Manish Gupta; Muthu Kumar Murugiah; Long Chiau Ming (Archives of Global Professionals, 2016)
Purpose: The aim of this review is to evaluate the safety and efficacy of a product named acai berry ABC and to understand the marketing issues implemented by this product. Methodology: A review regarding registration of product was conducted by examining the registration in Pharmaceutical Division Services, Ministry of Health of Malaysia and the profile of product was evaluated by assessing the online MIMS. Besides that, an electronic search was conducted through searching at Cochrane Library, EMBASE, PubMed to assess the safety and efficacy of the product. Malaysia Advertisement Board was referred to evaluate the marketing issue in acai berry ABC. Results: According to Pharmaceutical Division Services, Ministry of Health, acai berry ABC is listed under product adulterated with poison which is contained sibutramine as an active ingredient which is against the Sale of Drugs Act 1952. Acai berry ABC widely advertised throughout social media such as Facebook, website services, and online marketing. Thus, there are a few issues related to marketing that against the Medicine Advertisement Board. Moreover, a review on safety and efficacy of sibutramine reported that sibutramine is effective in weight loss and it also may increase slightly in blood pressure (BP). Sibutramine should be used cautiously in patients with borderline or high BP. However, the Sibutramine Cardiovascular Outcome Trial (SCOUT) trial showed that long-term use of sibutramine among the subject with cardiovascular disease had a risk of nonfatal myocardial infarction and nonfatal stroke, but not of cardiovascular death or death from any cause. Due to SCOUT trial, physician and pharmacist are recommended by the European Medicine Agency have to stop selling products containing sibutramine. Malaysia also banned this product since 2010. However, still there is a company selling the herbal weight loss product adulterated with sibutramine such as acai berry ABC. Conclusions: Ministry of Health has banned the selling of acai berry ABC in Malaysia due to adulteration with sibutramine which may risk and harmful to cardiovascular disease patient. As for Malaysian, it is not safe to consume the product that contains with control poison without consultation from physician or pharmacist. It is a pharmacist responsibility to educate people to consume an only product that registered with Ministry of Health. Malaysian should always consult with a physician or pharmacist if any confusion regarding any product that they have been consumed.